Immediate Lymphatic Reconstruction: Technical Points and Literature Review. Issue 2 (17th February 2021) - Coriddi, Michelle; Mehrara, Babak; Skoracki, Roman; Singhal, Dhruv; Dayan, Joseph H.
Abstract : Summary: Recent studies have provided evidence that lymphovenous bypass—microsurgical re-routing of divided lymphatics to an adjacent vein—performed at the time of lymph node dissection decreases the rate of lymphedema development. Immediate lymphatic reconstruction in this setting is technically demanding, and there is a paucity of literature describing the details of the surgical procedure. In this report, we review the literature supporting immediate lymphatic reconstruction and provide technical details to demystify the operation for surgeons who wish to provide this option to their patients.